PENGARUH KECERAHAN TERHADAP ENERGI LISTRIK YANG DIHASILKAN OLEH PANEL SURYA - Amin, Aditya Saputra; Ilham, Jumiati; Kamil Amali, Lanto M. (Journal Of Renewable Energy Engineering, 2024)
The reduction in fossil energy production, particularly petroleum, along with the global commitment to reducing greenhouse gas emissions, encourages the government to continuously improve the role of new and renewable energy to maintain energy security and independence. Renewable energy is a” source of energy derived from nature that can be used freely, continuously renewed, and unlimited, such as“solar energy. This study aims to analyze the performance of solar panels” in terms of battery charging and discharging duration, current, voltage, and power under sunny and cloudy conditions. The research method was conducted directly in the field, using a solar panel with a capacity of 10WP (Watt Peak) as the study object. The results showed that the performance of solar panels under sunny conditions achieved the highest average power of 4.81 Watts and the fastest battery charging time of 6 hours. Under cloudy conditions, the average power obtained was 4.34 Watts, and the battery charging time was 6 hours and 20 minutes. The battery discharging duration for a 5-watt lamp was 16 hours and 8 minutes, for a 10-watt lamp, it was 8 hours and 4 minutes, and for a 15-watt lamp, it was 5 hours and 6 minutes.